PENGARUH KETERLIBATAN KOMITE SEKOLAH TERHADAP KUALITAS KEPUTUSAN MANAJERIAL DI SEKOLAH MENENGAH SWASTA KECAMATAN BOJONGLOA KIDUL, KOTA BANDUNG - Devrinawati Situmorang; Suwito Eko Pramono; Agus Yuwono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the potential for agency problems in education management. The objective of this study was to analyze in depth the influence of school committee involvement on the quality of managerial decisions. This study used a quantitative approach with a correlational survey method. The research population includes school principals, teachers, and school committee members in private junior high schools (SMP) in Bojongloa Kidul District, Bandung City, with a purposive sampling technique used. The research results indicate a strong positive correlation between school committee involvement and the quality of managerial decisions, with a correlation coefficient of r=0.60. In more detail, school committee involvement was found to have a positive and significant influence on improving budget transparency and accountability (regression coefficient B=0.45), reducing information asymmetry (B=0.52), and aligning goal incongruence (B=0.38). In addition, this study also identified that support from the Education Office acted as a positive and significant moderating variable, which means that this support strengthened the relationship between school committee involvement and the quality of managerial decisions. In conclusion, active involvement of the school committee is effective in reducing agency problems and directly improves the quality of managerial decisions in schools. However, the effectiveness of the school committee's role is greatly influenced by the presence of systemic support from the Education Office.